PENERAPAN MODEL PEMBELAJARAN TIPE TEAM QUIZ DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS V UPTD SDN 188 BARRU - Risda; Asyifatul Haifa; Fitri Yanty Muchtar (STKIP Subang, 2024)
The learning model has a big influence on student learning outcomes. One element that influences learning is the learning model. This research focuses on the application of the team quiz type learning model in improving the mathematics learning outcomes of class V students at UPTD SDN 188 Barru, because mathematics is an abstract and deductive science so it requires a learning model that is able to understand students and provide curiosity about mathematics lessons. This research method is classroom action research (PTK) which includes four steps, namely planning, action, observation and reflection, and consists of two cycles. The subjects of this research were class V students of UPTD SDN 188 Barru in the 2024/2025 academic year. Data was collected through test techniques, observation, interviews and documentation. The research results show that implementing the Team quiz type learning model can improve student learning outcomes. There was a significant increase in students' academic achievement in mathematics subjects from cycles I and II, and the average mathematics test score increased in each cycle. In cycle I, the average score was 43.3 and the completion rate was 26.7%. In cycle II, the average score was 80 and the completion rate was 80%. Based on the research results, it can be concluded that the use of the Team quiz type learning model can improve student learning outcomes.